Responses of cowpea genotypes to indigenous rock phosphate application - Suzuki, K.; Fatokun, C.A.; Boukar, O. (Wiley, 2018)
Cowpea [Vigna unguiculata (L.) Walp.] plays an important role in the livelihoods of the people of sub-Saharan Africa, but phosphorus (P) deficiency in soils is a serious problem that contributes to low productivity. This study was conducted to verify the efficiency of indigenous rock phosphate (RP) as a P source to promote this affordable method of soil management to farmers. Pot experiments were conducted to identify good responder genotypes to RP application and its effect in cowpea cultivation using low-P soil from Fashola village in southwestern Nigeria and Togolese RP (34% P2O5). Shoot dry weight (SDW) at 8 wk after seeding (WAS) was significantly correlated with P uptake (r = 0.817; P < 0.01) and was therefore used as an indicator to select good responder genotypes. Sixteen of the 28 tested genotypes showed a low rate of decrease of SDW at 8 WAS under Togolese RP applications of 171 mg P kg–1 compared with 30 mg P kg–1 (as KH2PO4). Seven of these genotypes (Iron bean, IT87D-941–1, IT97K-499–38, DanIla, IT95K-1543, IT97K-556–4, and IT90K-284–2) showed a significantly higher SDW at 8 WAS compared with IT97K-499–35. In four of the seven good responders, the SDWs at 8 WAS were significantly higher and grain yield tended to be higher with ≥57 mg P kg–1 compared with zero application. Under field conditions, the micro-dosing technic is recommended for applying RP to avoid loss and to enhance the availability of P for cowpea cultivation.